2008
DOI: 10.1002/bio.1069
|View full text |Cite
|
Sign up to set email alerts
|

Humic acid–cetyltrimethylammonium bromide interaction: a fluorimetric study

Abstract: Synchronous and excitation emission matrix fluorescence (EEMF) characteristics of humic acid-surfactant interaction have been studied. The variation of synchronous and EEMF spectral maxima and intensities with humic acid (HA)-cetyltrimethylammonium bromide (CTAB) composition sensitively reflects the extent of flocculation of HA. It was found that the concentration range for co-precipitation of HA-CTAB was similar for all concentrations (60 p.p.m., 80 p.p.m. and 100 p.p.m.) of humic acid studied. In the concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…This may have lead to partial re-dispersion of the aggregates. Shang and Rice[110] and Subbiah and Mishra[111] investigated HA-C16TB complexes by,…”
mentioning
confidence: 99%
“…This may have lead to partial re-dispersion of the aggregates. Shang and Rice[110] and Subbiah and Mishra[111] investigated HA-C16TB complexes by,…”
mentioning
confidence: 99%
“…Secondly, the fluorescence peak had significant red shifts (peak a, from 447.5 nm to 468.0 nm; peak c, from 454.0 nm to 469.1 nm), implying that MG binding could induce micro-environmental changes of fluorophores groups in HA. In addition, peak b was looked like disappear and clearly quenched by MG comparing with peak a and peak b, which indicated that the humic-like substance obviously reacted with MG and MG could enter into the hydrophobic cavities of HA [22]. Fig.…”
Section: Fluorescence Quenching Of Ha By Mgmentioning
confidence: 88%
“…In addition, an obviously red shift of the HA fluorescence emission (from 455 nm to 469 nm) occurs. HA is a multichromophoric system which has different fluorescence groups [22]. The red shift of maximum emission wavelength suggested that the fluorescence groups were placed in a less hydrophobic environment and more fully exposed to the external environment [23].…”
Section: Fluorescence Quenching Of Ha By Mgmentioning
confidence: 99%
“…Therefore, many works have been carried out to characterize the binding of HA with some environmental pollutants. Subbian and Mishra have studied the interaction of humic acid with surfactant [10]. Nakashima et al have investigated the binding interaction of HA with heavy metal ions [8].…”
Section: Introductionmentioning
confidence: 98%
“…Humic acids (HA) are the major extractable component of soil humic substances and play a crucial role in removal and/or migration of environmental pollutants in natural water [8]. HA could bind with inorganic and organic contaminants through hydrophobic, electrostatic, hydrogen bonding, or coordinate bonding interaction [8,[10][11][12][13][14]. The binding constants and binding forces between environmental pollutants and HA are the great environmental concerns.…”
Section: Introductionmentioning
confidence: 99%